Submuscular Plate for Pediatric Femoral Fractures. Issue 1 (January 2017) - Shaner, Adam; Sponseller, Paul
Abstract : Management of pediatric femoral fractures is dependent on patient age and injury pattern. For length-stable femoral shaft fractures in school-age children (5 to 11 years of age), flexible intramedullary nailing (IMN) is a popular treatment method. However, for fracture patterns that are length-unstable or involve the proximal or distal third of the femur, flexible IMN has a higher rate of postoperative complications. Use of a submuscular bridge plate has been shown to be an effective alternative to IMN for these injuries. Because this long plate is inserted with a minimally invasive technique and indirect reduction, it acts as an internal type of "external fixator, " thereby avoiding soft-tissue stripping at the fracture site and decreasing strain across the fracture site.Postoperatively, patients begin hip and knee range-of-motion exercises without immobilization. Touch-down weight-bearing with crutches is used until callus formation is seen on radiographs, usually in 6 to 8 weeks. The plate can be removed 6 months after the index surgery. Step 1: Position the patient supine on a radiolucent table with a bump under the ipsilateral hip. Step 2: Lay a 4.5-mm narrow stainless-steel plate over the injured thigh and use fluoroscopy to determine the appropriate length for this plate. Contour the plate as needed. Step 3: Make a lateral, longitudinal incision of 2 to 3 cm at the proximal or distal part of the femur through the iliotibial band. Elevate the vastus lateralis extraperiosteally from the femur using a Cobb elevator. Pass the plate through this plane proximally or distally while maintaining contact between the plate and the femur. Step 4: Adjust the plate position using fluoroscopy. Obtain fracture reduction using closed techniques and secure the plate temporarily with Kirschner wires through the most proximal and distal holes. Step 5: Place the first screw near the end of the plate under direct visualization. Place the second screw using a percutaneous technique and insert it immediately proximal or distal to the fracture site where the femur is farthest from the plate. The drilling and length measurement of this screw are fluoroscopically aided and will bring the plate down into contact with the femoral cortex. Step 6: Place the remaining screws in a similar fashion; 3 screws proximal and distal to the fracture site provide adequate stability. Locking screws or lag screws are typically not necessary in this construct. Obtain final radiographs to ensure appropriate reduction length, alignment, and rotation.